The Russian Orthodox Church and atheism - Laitila, Teuvo (Approaching Religion, 2012)
After the collapse of the Soviet Union in 1991, the religious tide in Russia has been quick to rise. During the Soviet era, religion – particularly Orthodox Christianity and Islam – was considered to be one of the ‘enemies of the people’. Since the late 1990s however, Russian politicians at all levels of the power structure have associated themselves either with the Orthodox, or on some occasions with the Muslim, clergy. The present state of affairs in the relations between religion and the state are well illustrated by the cordial liaison of the late Patriarch Aleksii II with President Vladimir Putin and the equally warm involvement of President Dmitry Medvedev, and his wife Svetlana Medvedeva, with the new Patriarch Kirill, who was elected in January 2009. Some have even argued that ‘today’ (in 2004) the Church and state are so extensively intertwined that one can no longer consider Russia to be a secular state. Polls seem to support the claim. While in 1990 only 24 per cent of Russians identified themselves as Orthodox, in the sense that they felt themselves to be Russians as well, in 2008 the number was 73 per cent. However, less than 10 per cent, and in Moscow perhaps only 2 per cent do actually live out their religiosity.Why did Russia turn towards religion? Is religion chosen in an attempt to legitimise power, or in order to consolidate political rule after atheist-communist failure? My guess is that the answer to both is affirmative. Moreover, whatever the personal convictions of individual Russians, including politicians, religious, mainly Orthodox Christian, rhetoric and rituals are used to make a definitive break with the communist past and to create, or re-create, a Greater Russia (see Simons 2009). In such an ideological climate, atheism has little chance of thriving, whereas there is a sort of ‘social demand’ for its critique.I therefore focus on what the Russian Orthodox Church (ROC) has had to say about atheism and how her statements can be related to a break with the past and the construction of a new Russia. Or, in my opinion, actually deleting the Soviet period from the history of Russia as an error and seeing present-day Russia as a direct continuation of the pre-Soviet imperial state.